PELATIHAN KESIAPSIAGAAN KEBAKARAN DI PERMUKIMAN DESA TEPIAN MAKMUR - Erwin, Erwin; Mubayanah, Isna Rofiatul; Mubarok, Ramdanil; Mutasyarifin, Aham (P3M STAI Sangatta, 2024)
Fire is a serious threat to settlements, both urban and rural. To improve the response to the fire threat, a fire preparedness training program is being conducted in the settlements. The purpose of this report is to present the implementation, results, and evaluation of the fire preparedness training program in the settlement conducted by the PkM team. The method used is the Participatory Action Research method. (PAR). This dedication is held in the village of Tepian Makmur, in the district of Rantau Pulung, East Kutai district. The fire preparedness training program in this settlement has improved public response to the fire threat. Active public participation, increased knowledge and skills of participants, as well as positive feedback, are indicators of the success of the program. Fire preparedness training in settlements is an effective step in improving response to fire threats. This program could be a model for similar efforts elsewhere to improve public preparedness for fire disasters.